Population Dynamics of Jinga Shrimp (Metapenaeus affinis) in Samboja Kuala Waters Kutai Kartanegara Regency - Jahrah, Fatimah; Ramang, Muhammad Syahrir; Susilo, Heru; Susanto, Adi; Irawan, Aditya; Erwiantono , Erwiantono (Torani Journal of Fisheries and Marine Science, 2023)
Pink shrimp (Metapenaeus affinis) or Jinga shrimp is one of the species caught in the waters off Samboja Kuala. This catch is a valuable commodity in the market. The possibility of exploiting shrimp resources will be jeopardized in an effort to conserve, utilize, and catch high intensity shrimp. This study was conducted from September to December 2022 with the aim of determining population dynamics parameters using the frequency method from carapace length data. A mini trawl was used to collect shrimp in the waters of Samboja Kuala, Kutai Kartanegara Regency. Male and female jinga shrimp have a ratio of 1:2,43. Furthermore, for male and female shrimp, the growth rate coefficient (K) was 0,580 and 14,00, respectively, and the approximated natural length (L) was 145.82 and 160.81. Pink shrimp (Metapenaeus affinis) have natural mortality (M) of 1,113/year, mortality due to capture (F) of 0,516, and total mortality (Z) of 1,630, with exploitation value (E) of 0,316, indicating that they are still at the appropriate level. Herefore, female shrimp peaked in August at 14,6% and males peaked in July 31,81%. The Y/R capability was 0,049/year, and Emax calculated the Y/R relationship with the exploitation rate, which was 0,42.